Organization of Activity as a Criterion for Classification of Volunteering - Koval, Hennadiy (Psychological Prospects Journal, 2017)
The interdependence of various aspects of the definition of volunteerism in their correlation with levels realization volunteer activity was considered in the article.The levels of activity realization have been brought in accordance with the taxonomy of objects of socio-psychological study.Generalizing model of the correlation of various levels of volunteering with the subjects of the volunteer activity through the subsystem of activity, which determines the different way the organizationally accompany   the activity of a particular subject have been proposed. That has been allowed to substantiate the notion of organizing the activity as a criterion for the classification of manifestations of volunteering.The subsystem of organizationally accompany of activity was disclosed through the notion of the structure of activity, which has been singled out within the general psychological theory of activity. In which the structural elements of activities such as activities, action, operation has been associated with the concepts of motive, goal and condition. The possibility of generalizing variables that direct the structural elements of activities through the notion of organizationally the subsystem of activity was disclosed. The specific difference in the volunteer activities self-organization at the levels of its realization by the person and the social movement has been disclosed through the notion of substructures of activities. That is causes the need for further analysis of the mutual influence of these variables in their providing a concrete volunteer activity, which is realized by the person as a participant in the social movement.
Keywords: volunteering,subject of activity, structure of activity, organization of activity, levels realization of activity.